olve the system of two equations using substitution.

y=2+3x
4x−3y=−16

1 answer

First, solve the first equation for y in terms of x:

y = 2 + 3x

Next, substitute this expression for y into the second equation:

4x - 3(2 + 3x) = -16
4x - 6 - 9x = -16
-5x - 6 = -16
-5x = -10
x = 2

Now that we have found the value of x, we can substitute it back into the first equation to find y:

y = 2 + 3(2)
y = 2 + 6
y = 8

Therefore, the solution to the system of equations is x = 2 and y = 8.
Similar Questions
  1. Solving Equations Using Substitution Quick Check1 of 51 of 5 Items Question Solve the system of two equations using
    1. answers icon 11 answers
  2. Solving Equations Using Substitution Quick Check1 of 51 of 5 Items Question Solve the system of two equations using
    1. answers icon 17 answers
  3. 1. For the following system of equations, what is the x-value of the solution?-x+2y=6 6y=x+18 a. -18 b. 0*** c. -6 d. 3 2. Solve
    1. answers icon 48 answers
    1. answers icon 1 answer
more similar questions